Efficiency of Acidulated Low Grade Udaipur Rock Phosphate with Sulphuric Acid and Phosphoric Acid - Yadav, B k; Swami, B N; Tarafdar, J C (Annals of Arid Zone, 2016)
The present investigation was conducted for evaluating 'partially acidulated low grade Udaipur rock phosphate with 10, 20, 30 and 40%, sulphuric acid, phosphoric acid and their mixture in equal proportions. In incubation studies, superphosphate, untreated rock phosphate and different types of partially acidulated rock phosphate @ 200 mg kg-I of soils were added and incubated for 15, 30, 45 and 60 days. Total phosphorus content in partially acidulated rock phosphate decreased successively with increasing levels of sulphuric acid. However, a reverse trend was recorded on acidulation with phosphoric acid. Water-soluble phosphorus, citrate soluble phosphorus and available phosphorus increased with the increasing levels of the acids namely H2S04, 1'13P04 and their mixture in equal proportions. However, citrateinsoluble phosphorus fraction decreased with increasing levels of all the acidulents. Available phosphorus (Olsen's P) in incubated soils and relative efficiency of partially acidulated rock phosphate (PARP) increased significantly, with the maximum value under 40% in partially acidulated with phosphoric acid treatment. The relationships between different P constituents of partially acidulated rock phosphate with available (Olsen's) phosphorus (except citrate-insoluble) in the soils at different periods of incubation showed positive significant correlation.